STORE IMAGE, STORE SATISFACTION DAN STORE LOYALTY DALAM KEGIATAN BELANJA KONSUMEN - Singgih Santoso (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2009)
In marketing literature, there were many discussions about relations between consumer satisfaction and consumer loyalty. Many researchers believe that satisfied consumer will tend to be loyal, and consumer satisfaction could be influenced by many factors, that if being applied to a shopping situation, this factor is store image. Main objective of this research is to know whether there was significant relation between store image with store satisfaction, and significant relation between store satisfactions with store loyalty. The research, which being held in December 2007, was conducted to the consumers who shopped in Carrefour , involved one hundred respondents. Data analysis with regression model give results that store image did not have relation with store satisfaction. Also found that store satisfaction evidently did not have relation with store loyalty. Those results could be caused by the existence of several other variables that were stronger in influencing relations between store the image, store satisfaction and store loyalty, like customer relationship, the positive effect, perceived risk, category experience, consumer commitment, and value/cost ratio that could make consumer switching to the other supermarket.